2010
DOI: 10.1111/j.1365-2125.2010.03634.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and plasma steady‐state pharmacokinetics of raltegravir, darunavir, etravirine and ritonavir in heavily pre‐treated HIV‐infected patients

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The combination of raltegravir, etravirine and ritonavir boosted darunavir is a potent antiretroviral regimen for patients who have been heavily pre-treated for HIV-infection. All these agents have to exert their action intracellularly. However, only little is known about the cellular pharmacology of these agents. WHAT THIS STUDY ADDS• We investigated the steady-state plasma and cellular pharmacokinetics of raltegravir, etravirine, darunavir and ritonavir and the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 28 publications
5
33
6
Order By: Relevance
“…The intracellular-to-plasma ratios for RAL were only 0.11 to 0.24 in our study using two different methods of estimation. This result is consistent with other studies of HIV patients on standard doses (19) and an 800-mg once daily (15) dose of RAL. This result is also consistent with simple diffusion of unbound RAL into cells, based on protein binding of 83% in plasma (14).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The intracellular-to-plasma ratios for RAL were only 0.11 to 0.24 in our study using two different methods of estimation. This result is consistent with other studies of HIV patients on standard doses (19) and an 800-mg once daily (15) dose of RAL. This result is also consistent with simple diffusion of unbound RAL into cells, based on protein binding of 83% in plasma (14).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, at least two studies reported that a one-compartment model provided an adequate data fit. Our healthy subjects had lower population mean (%RSE) CL/F, 39.1 (20.8%) liters/h compared to 264 (23%) and 191 (16%) liters/h in the study of Dickinson et al (4) and Ter Heine et al (19), respectively. For V/F, our study yielded 272 (21.8%) liters in comparison with 820 (25.5%) (4) and 76 (8%) liters (19).…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations